2017
DOI: 10.1097/olq.0000000000000581
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Potential Harms of Human Immunodeficiency Virus Self-Testing Among Men Who Have Sex With Men in China: An Implementation Perspective

Abstract: Background HIV self-testing (HIVST) holds great promise for reaching high-risk key populations who do not access facility-based services. We sought to characterize unsupervised HIVST implementation among men who have sex with men (MSM) in China. Methods We conducted a nationwide online survey in China. Eligible men were at least 16 years, had anal sex with a man, and had recent condomless sex. We assessed benefits (first-time testing, increased testing frequency, confirmatory testing) and potential harms (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 22 publications
(36 reference statements)
6
48
0
Order By: Relevance
“…Similar to other studies in Chinese MSM, in this study MSM recruited via the internet, compared to other MSM, had a higher income, were more likely to use illicit drugs, had previously tested for HIV less frequently, and were likely to seek male sex partners and HIV knowledge or HIV intervention programmes online . These findings also suggest that online interventions could reach internet‐using MSM at high risk of HIV infection in China.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to other studies in Chinese MSM, in this study MSM recruited via the internet, compared to other MSM, had a higher income, were more likely to use illicit drugs, had previously tested for HIV less frequently, and were likely to seek male sex partners and HIV knowledge or HIV intervention programmes online . These findings also suggest that online interventions could reach internet‐using MSM at high risk of HIV infection in China.…”
Section: Discussionsupporting
confidence: 84%
“…This suggests that there is great scope for promoting oral HIVST among internet‐using MSM who have not conducted HIVST but are willing to do so. A study reported that 31% of internet‐using Chinese MSM tested for HIV used HIVST as their first HIV test . Studies in the USA demonstrated that internet‐using MSM, especially those who had never tested for HIV or who had CAI, preferred oral HIVST to any other testing strategies, such as VCT .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dedication of peer educators in supporting clients with reactive results to access confirmatory testing and ART services is thought to have contributed to the linkage results. Data are limited on lay provider testing and self‐testing among PWID, FSWs and partners of PLHIV but previous studies on HIV self‐testing among MSM show lower but still impressive linkage, for example, 77.5% in China and 78% in the United Kingdom .…”
Section: Discussionmentioning
confidence: 98%
“…The high linkage in that study was likely due to follow-up calls after HIVST distribution, the ease of participant's access to the opinion leaders and also the linkage to a well-trusted MSM-friendly facility that offers HIV prevention services. Studies conducted in other areas reported both fairly low [22] and high [23], [24]. linkage to HIV care and treatment after self-testing.…”
Section: Discussionmentioning
confidence: 94%